Isolation of a virus with rhabdovirus morphology from a white-beaked dolphin (Lagenorhynchus albirostris). - Osterhaus, A.D.M.E. (Albert); Broeders, H.W.J.; Teppema, J.S.; Kuiken, T. (Thijs); House, J.A.; Vos, H.W. (Helma); Visser, I.K.G. (Ilona) (Archives of Virology, 1993)
A virus with rhabdovirus morphology which proved to be antigenically distinct from rabies virus and vesicular stomatitis virus was isolated from a dolphin that had beached on the Dutch coast. Neutralizing antibodies to this virus were found in several European marine mammal species.